Self-assembly of endohedral metallofullerenes: a decisive role of cooling gas and metal–carbon bonding. Issue 6 (27th January 2016) - Deng, Qingming; Heine, Thomas; Irle, Stephan; Popov, Alexey A.
Abstract : Molecular dynamics simulations of the endohedral metallofullerene formation reveal a crucial role of the cooling gas (He) and the strength of metal–carbon bonding in the formation mechanism. Abstract : The endohedral metallofullerene (EMF) self-assembly process in Sc/carbon vapor in the presence and absence of an inert cooling gas (helium) is systematically investigated using quantum chemical molecular dynamics simulations. It is revealed that the presence of He atoms accelerates the formation of pentagons and hexagons and reduces the size of the self-assembled carbon cages in comparison with analogous He-free simulations. As a result, the Sc/C/He system simulations produce a larger number of successful trajectories ( i.e. leading to Sc-EMFs) with more realistic cage-size distribution than simulations of the Sc/C system. The main Sc encapsulation mechanism involves nucleation of several hexagons and pentagons with Sc atoms already at the early stages of carbon vapor condensation. In such proto-cages, both Sc–C σ-bonds and coordination bonds between Sc atoms and the π-system of the carbon network are present. Sc atoms are thus rather labile and can move along the carbon network, but the overall bonding is sufficiently strong to prevent dissociation even at temperatures around 2000 kelvin. Further growth of the fullerene cage results in the encapsulation of one or two Sc atoms within the fullerene. In agreement with experimental studies, an extension of the simulations to Fe and Ti as the metal component showed that Fe-EMFs are not formed at all, whereas Ti is prone to form Ti-EMFs with small cage sizes, including Ti@C28 - T d and Ti@C30 - C 2v (3).